Effect of fabric mulch ground covers on lemon trees rhizosphere microbiome in Florida flatwood soils - Santiago, John M.; Fox, John-Paul; Guzmán, Sandra M.; Rossi, Lorenzo (Frontiers in Soil Science, 2023)
The rhizosphere community composition has been shown to provide benefits in nutrient acquisition and plant health. Furthermore, rhizosphere communities can be heavily influenced by cultural practices in citrus production systems, providing benefits in soil and root health, and plant physiology. Florida growers are implementing new and more sustainable soil management practices, such as using fabric mulch ground covers to improve weed and pest control, while retaining soil moisture. Little is known regarding the influence of these ground covers on the rhizosphere microbial communities of lemon trees, especially under endemic Huanglongbing pressure. Understanding how lemon roots and the rhizosphere microbiome are influenced by fabric mulch ground covers can potentially lead to improved management practices. The aim of this research was to evaluate the effects of fabric mulch ground covers on lemon tree rhizosphere health. Plant material consisted of four-year old lemon trees cv. ‘Meyer’ (Citrus limon) grafted on ‘sour orange’ (Citrus × aurantium) rootstocks. The experiment consisted of two treatments, which included trees grown with fabric mulch ground covers and trees grown without fabric mulch ground covers. Rhizosphere DNA was extracted, sequenced, and analyzed to assess differences in diversity and composition (alpha and beta diversity) of rhizosphere bacteria among treatments. Obtained results showed that lemon trees treated with fabric mulch ground covers had significantly greater rhizosphere bacterial diversity when compared to the uncovered trees.